Complex sclerosing lesions and radial sclerosing lesions on core needle biopsy: Low risk of carcinoma on excision in cases with clinical and imaging concordance. Issue 2 (7th July 2017) - Nakhlis, Faina; Lester, Susan; Denison, Christine; Wong, Stephanie M.; Mongiu, Anne; Golshan, Mehra
Abstract: Complex or radial sclerosing lesions (CSL/RSL) are uncommon diagnoses on core needle biopsy with a reported upgrade rate ranging between 0% and 23%. As a result, their management remains controversial. In this study, we sought to determine the rate of malignancy on excision for patients with pure CSL/RSL on core biopsy, and to evaluate future breast cancer risk when CSL/RSL is managed without excision. We retrospectively reviewed 118 cases of CSL/RSL diagnosed on image‐guided breast biopsies between 2005 and 2014 at our institution. Of 98 analyzed patients, 34 (35%) underwent excision and 64 (65%) were observed. Demographic and clinical variables between excision and observation groups were compared. In excised specimens, factors associated with upgrade to malignancy were evaluated. The median age at diagnosis was 49 years (range, 27‐88 years). In the excision group, 3/34 cases were associated with malignancy, an overall upgrade rate of 9%. All malignant cases had core needle biopsies interpreted as discordant and were BIRADS 4B or more on imaging. In the observation group, at a median follow‐up of 2.2 years, 3/64 (5%) patients developed ipsilateral cancers, all of which were distant from the index CSL/RSL. In our series, we report a 9% malignancy rate on excision of BIRADS >4C lesions characterized as CSL/RSL on core biopsy. In patients with concordant biopsies and BIRADS 4A or lower lesions who underwent observation, we found a low rate of subsequent ipsilateral cancers. Further studies are needed to confirm that for CSL/RSL in concordant core biopsies and BIRADS 4A or lower, nonpalpable lesions, observation may be a reasonable alternative to excision.